Governare le economie locali. Tradizione civica e neomunicipalismo per la gestione dei beni comuni - Pazzagli, Rossano (Scienze del Territorio, 2018)
The centrality of territory and the revalorisation of the local dimension compel for defensive strategies to safeguard basic institutions, and especially municipalities, intended as main institutional references of local economic systems. This paper describes the historic processes of economic deterritorialisation and marginalisation of inland areas, while raising the issue of territorial regeneration as strategic focus for overcoming the neo-liberal drift of economic development and the territorial unbalances characterising the Italian situation. Today, enduring processes of liberalisation, privatisation and power concentration resulted in the inhibition of endogenous forces for local development, in the weakening of democracy and in the curtailment of self-governance spaces. It is therefore urgent to activate sound strategies for the empowerment of local communities. The paper attributes a key role to municipalities: municipal institutions, historically modelled on territories, represent the pivotal element of a solid civic tradition that from Middle Ages continued up to the time of the republican Constitution. Nevertheless, institutional policies eventually undermined local autonomies, even trying to reduce the number of municipalities. This paper aims at proving that municipal autonomy, linked to the identity, culture, environment and quality of life characteristic of great part of the Italian territory, represents a significant component of territorial heritage.